2009
DOI: 10.1051/0004-6361:200810274
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of luminosity functions: the 2dFGRS example

Abstract: Aims. We use the 2dF Galaxy Redshift Survey to derive the luminosity function (LF) of the first-ranked (brightest) group/cluster galaxies, the LF of second-ranked, satellite, and isolated galaxies, and the LF of groups of galaxies. Methods. We investigate the LFs of different samples in various environments: in voids, filaments, superclusters, and supercluster cores. We compare the derived LFs with the Schechter and double-power-law analytical expressions. We also analyse the luminosities of isolated galaxies.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 124 publications
(191 reference statements)
2
73
0
Order By: Relevance
“…The faint-end of the LF of the most dense environments is slightly different, but the number of galaxies in this region is also small and the dip of the LF may be caused purely by selection effects in the SDSS, as mentioned above. The bright-end of the LF of the least dense environments is also slightly different from that in other environments, because generally, very bright galaxies are absent from the low density environments (Tempel et al 2009). …”
Section: Luminosity Functions In Different Environmentsmentioning
confidence: 88%
See 2 more Smart Citations
“…The faint-end of the LF of the most dense environments is slightly different, but the number of galaxies in this region is also small and the dip of the LF may be caused purely by selection effects in the SDSS, as mentioned above. The bright-end of the LF of the least dense environments is also slightly different from that in other environments, because generally, very bright galaxies are absent from the low density environments (Tempel et al 2009). …”
Section: Luminosity Functions In Different Environmentsmentioning
confidence: 88%
“…In Tempel et al (2009) A&A 529, A53 (2011) we have found that the global environment has an important role in determining galaxy properties. Some studies have been dedicated only to special regions: e.g., Mercurio et al (2006) investigate the Shapley supercluster.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In each region some galaxies are single. They may be the brightest galaxies of faint groups in which other member galaxies are too faint to be observed within SDSS survey magnitude limits (Tempel et al 2009). We estimated the masses of these faint groups using the number of single galaxies in a region, and median masses of groups with less then five member galaxies.…”
Section: Masses and Mass-to-light Ratiosmentioning
confidence: 99%
“…For example, rich superclusters contain high-density cores that may contain merging X-ray clusters and may be collapsing (Small et al 1998;Bardelli et al 2000;Einasto et al 2001;Rose et al 2002;Einasto et al 2007cEinasto et al , 2008. A supercluster environment with a wide range of densities affects the properties of galaxies, groups, and clusters located there (Einasto et al 2003b;Plionis 2004;Wolf et al 2005;Haines et al 2006;Einasto et al 2007d;Porter et al 2008;Tempel et al 2009;Fleenor & Johnston-Hollitt 2010;Tempel et al 2011;Einasto et al 2011b). Einasto et al (2011b) showed that the dynamical evolution of one of the richest superclusters in the Sloan Great Wall (SCL 111, SCl 024 in L10 catalogue) is almost finished, while the richest member of the Wall, SCl 126 (SCl 061) is still dynamically active.…”
Section: Discussionmentioning
confidence: 99%